Exploring factors influencing recreational experiences of urban river corridors based on social media data - Shi, Lin; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari; Dai, Chenyang (Multidisciplinary Digital Publishing Institute, 2024)
River corridors, recognized as “blue–green infrastructure,” have become a crucial support system for urban sustainability in contemporary urbanized societies. Understanding the factors influencing the recreational experience along urban river corridors is paramount for enhancing visitors’ health and well-being. This study focuses on the Hutuo River Corridor in Shijiazhuang, China, collecting 3006 valid reviews from Dianping, a prominent review platform. We developed a text-based thematic model and conducted content analysis using this dataset. The main social (visiting time, duration of stay, motivation, safety, and visitors’ types and activities) and physical (natural elements, artificial facilities, maintenance and management, accessibility, distance, models of transportation, weather, and seasons) factors associated with recreational experiences were identified. We assessed visitor perceptions of urban river corridors and elucidated facilitators or barriers through textual content analysis in reviews. The results indicate the feasibility of employing social media data to study visitors’ recreational experiences along urban river corridors. This comprehensive exploration from a qualitative ecological perspective contributes valuable insights for urban planning and management. Moreover, the findings hold significant implications for understanding the usage patterns of river corridors in China and potentially in other countries.